INVESTIGASI LAJU REGANGAN CREEP BAJA TAHAN KARAT FERRITIC PADA TEMPERATUR 570 °C - Ekaputra, I Made Wicaksana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The probabilistic assessment of failure due to the creep phenomenon must be determined with the minimum deviation. Since the creep failure took years before rupture, laboratory experiments were conducted to represent the failure time. However, the laboratory results are only an empirical approach; therefore, the probabilistic assessment can be deviated. A huge number of variables in creep experiments must be conducted to minimize the deviation. This study investigated the creep strain rate for the 9Cr-1Mo ferritic stainless steel. The lever-arm creep machine was used for the creep rupture test, and the test followed the standard of ASTM E139. The constant loads were applied in the range of 250 – 170 MPa with the homologous temperature of 570 °C. The curve of strain to time was recorded from each constant load condition. The creep strain rate was then calculated and presented in the curve of the creep strain rate to the applied load. The linear regression was drawn from the curve by applying Norton’s equation. By obtaining the creep strain hardening coefficient and exponent, an initial probabilistic assessment of creep failure at a temperature of 570 °C can be predicted.